Conformational Analysis and Through‐Chain Charge Propagation in Ferrocenyl‐Conjugated Homopeptides of 2, 3‐Diaminopropionic acid (Dap). Issue 6 (21st January 2022) - Biondi, Barbara; Bisello, Annalisa; Cardena, Roberta; Schiesari, Renato; Facci, Martino; Cerveson, Laura; Rancan, Marzio; Formaggio, Fernando; Santi, Saverio
Abstract: This work reports a detailed conformational and electrochemical study of two series of ferrocene (Fc)‐peptide conjugates, based on the side‐chain protected, 2, 3‐diaminopropionic acid (L−Dap). In one series Fc is linked to the N‐terminus, in the other to the C‐terminus of the Dap homo‐peptides. The conformational analysis carried out in solution (IR absorption and NMR) and in the crystal state (X‐ray diffraction) suggests that these peptides adopt a 310 ‐helical structure. Cyclic voltammetry showed that the peptide length positively or negatively affects the oxidation potential of Fc. The two opposite trends are correlated to the different orientation of the macrodipole moment of the 310 ‐helix in the two series with respect to the position of the Fc group in the chain. Finally, the variation of the IR absorptions upon chemical oxidation indicates that our 310 ‐helical conjugates are very efficient in transferring the positive charge along the peptides through the H‐bond network. Abstract : An in‐depth conformational and electrochemical study of two Fc‐conjugated, homo‐peptide series, based on the Boc‐protected 2, 3‐diaminopropionic acid, L−Dap(Boc), suggests that they adopt a 310 ‐helical structure. The variation of the IR absorptions upon chemical oxidation strongly supports the view that these Fc‐peptides are particularly efficient in conveying the positive charge along the backbone, through the H‐bond network.